Math anxiety, self-regulated learning, and academic procrastination in class VIII Students: A case study at SMPN 2 Alalak - Atsnan, Muh Fajaruddin; Sabirin, Muhamad; Mardhatillah, Nadia; Nareki, Maisea Ledua; Gazali, Rahmita Yuliana; Fajaruddin, Syarief (Research and Social Study Institute, 2023)
The research aimed to (1) determine students' math anxiety levels, (2) know the level of students' self-regulated learning, (3) know the level of student academic procrastination, (4) determine the relationship between math anxiety and students' academic procrastination, (5) and determine the relationship between self-regulated learning and students' academic procrastination. The quantitative research method used correlational research, which is used to determine the relationship between two or more variables. The population was 152 students in class VIII of SMPN 2 Alalak. Samples were 62 students and were selected using a cluster random sampling technique. Data collection techniques were questionnaires, interviews, and documentation. The data analysis technique used descriptive analysis and hypothesis test using the Spearman rank correlation test. The finding showed that, first, the student's math anxiety level is in the medium category with a percentage of 62.90%. Second, the students' self-regulated learning level is in the medium category with a percentage of 54.84%. Third, the level of student academic procrastination is in the medium category, with a percentage of 75.81%. Fourth, there is a positive relationship between math anxiety and students' academic procrastination in Mathematics subjects in class VIII SMPN 2 Alalak. And there is a negative relationship between self-regulated learning and students' academic procrastination in Mathematics in class VIII SMPN 2 Alalak.